ABLATION FOR UNINTERRUPTEDLY RECURRENT VENTRICLE TACHYCARDIA - G. V. Kolunin; A. V. Pavlov; D. V. Belonogov; V. E. Kharats; A. L. Ulyanov (Инновационная медицина Кубани)
We present a clinical case with continuous recurrent ventricle tachycardia. Patient, 60, admitted with complaints on heart disorders, periods of unexpected total weakness, repeated episodes of pre-syncopal condition, frequent dizziness, which he has been experiencing for about a year. In the anamnesis patient had diagnosis of intermittent syndrome WPW with paroxysmal antidromic tachycardia, and we performed ablation for additional conducting atrioventricular connection. By results of examination we recommended ablation of arrhythmia substrate with the subsequent solution whether implantation of a cardioverter defibrillator was required. Stimulation and activation mapping was performed. The area of ventricular tachycardia substrate was defined in the septal part of the right ventricle outflow tract, and frequent ventricular ectopic activity – in the area of the anterio-lateral wall of LV outflow tract under the aortal valve. On the basis of radiofrequency impact series we observed ventricular disturbances discontinuation. After the performed operation the patient demonstrated clinical improvement. According to Holter ECG monitoring for jogging of group ventricular activity, and also ventricular tachycardia was not registered.